Implementation of the rme model using the ctl approach on mathematics learning outcomes - Tiara Ayu Linggar Sari; Bambang Agus Sulistyono; Samijo Samijo (Hipotenusa Journal of Research Mathematics Education (HJRME), 2026)
Mathematics instruction in high school continues to face the challenge of low student achievement, particularly regarding the abstract concept of tangents to circles. This situation indicates that the learning process has not fully connected mathematical concepts to students’ real-life contexts, resulting in suboptimal conceptual understanding. This study aims to determine the effectiveness of applying the Realistic Mathematics Education (RME) model with the Contextual Teaching and Learning (CTL) approach in improving students’ mathematics learning outcomes. This study uses a quantitative approach with a one-group pretest–posttest experimental design. The research subjects were 33 students in class XI-6 at SMA Negeri 3 Kediri. Data collection was conducted through pretest and posttest assessments. The data were analyzed using descriptive statistics, a normality test, a paired-sample t-test, and an N-Gain test. The results showed that the average pretest score of 44.55 increased to 80.00 on the posttest. The results of the paired-sample t-test showed a significance level of less than 0.05, indicating a significant difference between learning outcomes before and after the intervention. The N-Gain value of 0.62 falls into the moderate category. These findings suggest that the implementation of the RME model with the CTL approach is effective in improving students’ mathematics learning outcomes and helps students better understand the concept of tangent lines to a circle.